Psalm 78: A Case Study in Redaction as Propaganda - Tammuz, Oded (The catholic biblical quarterly, 2017)
The original version of Psalm 78 was written in the northern kingdom. Its original purpose is not known, but its topic is clear: God's continued benevolence to the people of Israel despite their disobedience and disloyalty. During the reign of King Zedekiah o f Judah (597-586 b.c.e.), there was, on one side, a faction that advocated rebelling against the Babylonians and, on the other side, people such as the prophet Jeremiah who argued against rebelling. A member of the former faction (the redactor o f Psalm 78) took it upon himself to write a document that would support his side. The basis o f the new document was the original version o f Psalm 78, which was widely known in Judah. The redaction included additions and alterations on a very small scale (w. 4a and 9-10 were added, and w . 67-71 were altered). Two methods were used in the redaction: (1) working from the outside inward, and (2) detournement. The secondary purpose of the redaction was to explain v. 57b, which the redactor did not understand.